MEDICINES AFFECTING METABOLISM (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The endocrine system plays an important role in the body. The internal secretory glands that enter it produce biologically active substances - hormones during their activity. They participate in and control various physiological processes of the body necessary for life. More precisely, the central nervous system, with the help of the hormones of these internal secretion glands, ensures the normal passage of various physiological processes in the body. This article provides information about drugs that affect metabolism.